2020
DOI: 10.1109/access.2020.3009665
|View full text |Cite
|
Sign up to set email alerts
|

S-EEGNet: Electroencephalogram Signal Classification Based on a Separable Convolution Neural Network With Bilinear Interpolation

Abstract: As one of the most important research fields in the brain-computer interface (BCI) field, electroencephalogram (EEG) classification has a wide range of application values. However, for the EEG signal, it is difficult for the traditional neural networks to capture the characteristics of the EEG signal more comprehensively from the time and space dimensions, which has a certain effect on the accuracy of EEG classification. To solve this problem, we can improve the accuracy of classification via end-to-end learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Separable convolutions have been widely used in the field of deep learning (Zhang et al, 2017 ; Zhang R. et al, 2019 ; Huang et al, 2020 ). It divides a kernel into two smaller kernels, were most common is to divide a 3*3 kernel into a 3*1 and 1*3 kernel.…”
Section: Resultsmentioning
confidence: 99%
“…Separable convolutions have been widely used in the field of deep learning (Zhang et al, 2017 ; Zhang R. et al, 2019 ; Huang et al, 2020 ). It divides a kernel into two smaller kernels, were most common is to divide a 3*3 kernel into a 3*1 and 1*3 kernel.…”
Section: Resultsmentioning
confidence: 99%
“…The first model to use this layer for EEG analysis is EEGNet [21], which has been successful in the field of brain-computer interface. Huang et al [22] also reported the effectiveness of the EEGNet-based model in their study of EEG-based emotion classification tasks . Using an extended model of EEGNet, Shoji et al [23] successfully identified abnormal EEG durations indicative of patients with juvenile absence epilepsy.…”
Section: Separable Convolutionmentioning
confidence: 99%
“…Since EEG signals can also be viewed as images, many researchers recently have applied interpolation algorithms to enhance spatial structure of EEG. For example, Huang et al [11] proposed a separable convolutional neural network(CNN) with bilinear interpolation in brain-computer interface for EEG classification. Svantesson et al [38] utilized CNN as interpolation method to upsample and restore channels, which finally recreate EEG signals with a higher accuracy.…”
Section: Eeg Interpolation Algorithmsmentioning
confidence: 99%